2010
DOI: 10.1111/j.1365-2567.2009.03201.x
|View full text |Cite
|
Sign up to set email alerts
|

Extensive major histocompatibility complex class I binding promiscuity for Mycobacterium tuberculosis TB10.4 peptides and immune dominance of human leucocyte antigen (HLA)‐B*0702 and HLA‐B*0801 alleles in TB10.4 CD8+ T‐cell responses

Abstract: Subsequent construction of tetramers allowed us to confirm the recognition of some of the epitopes by CD8 + T cells from patients with active pulmonary TB. HLA-B alleles served as the dominant MHC class I restricting molecules for anti-Mtb TB10.4-specific CD8 + T-cell responses measured in CD8 + T cells from patients with pulmonary TB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 42 publications
4
49
0
1
Order By: Relevance
“…These studies suggest that this observation is not limited to RNA viruses. In fact it has even been described for an intracellular bacterial pathogen, Mycobacterium tuberculosis (76, 77). Furthermore, HLA B restricted T cell responses have been described to be of higher magnitude (73) and have been described to influence infectious disease course and outcome.…”
Section: Discussionmentioning
confidence: 99%
“…These studies suggest that this observation is not limited to RNA viruses. In fact it has even been described for an intracellular bacterial pathogen, Mycobacterium tuberculosis (76, 77). Furthermore, HLA B restricted T cell responses have been described to be of higher magnitude (73) and have been described to influence infectious disease course and outcome.…”
Section: Discussionmentioning
confidence: 99%
“…These data are best explained by a model in which the T-cell clone recognizes Rv2034 p81–100 and Rv2034 p88–107 via multiple HLA molecules, possibly including HLA-DR2, -DR3 as well as HLA-DQ1 registers, but that the dominant response to the protein is HLA-DR restricted. Such promiscuous peptides, capable of being presented by multiple HLA molecules, have been shown for several mycobacterial proteins [56], including HspX (16 kDa protein) [57], TB10.4 [58] and Hsp65 [59]. In addition, some ( Mtb antigen) studies showed possible presentation of a single epitope, specific for one clone, via both HLA-DR and HLA-DQ [57], [60].…”
Section: Resultsmentioning
confidence: 99%
“…Epitope promiscuity has been shown both experimentally and computationally for peptides derived from different pathogens, including the human papillomavirus [16], HIV [11,15,17,18], and M. tuberculosis [14,32], among others [9,10,12,13]. However, to our knowledge, this is the first study that directly compares promiscuity in multiple pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown in a variety of pathogens that, even though the adaptive immune response is highly specific, individual HLA class II-restricted peptides [9-13] and HLA class I-restricted peptides [14-18] may bind many different HLA alleles; a trait termed epitope promiscuity. Given the extensive human HLA allele diversity and varied pathogen epitope diversity, we were interested in determining whether the extent of epitope promiscuity varies in pathogens with distinct ecological niches and interactions with human hosts.…”
Section: Introductionmentioning
confidence: 99%